IMPACT OF THE LEGISLATION IN INFORMAL ECONOMY OF SOUTH – EASTERN EUROPEAN COUNTRIES – WITH PARTICULAR FOCUS IN KOSOVO - Krasniqi, Armand (Journal of Advanced Research in Law and Economics; Vol 1 No 2 (2010): JARLE volume 1 Issue 2(2) Winter 2010, 2017)
In several South Easter European Countries due to the delayed transition, the legal system of the economy is regulated with certain inappropriate provisions which reflect a weak institutional control system and inefficient implementation of sanctions against entities – operators that are not registered which realistically belong to the business activities. Through informal economy channels, which in some particular countries include a high percentage of the movement of goods and services, there is a specific traffic that takes places which actually scores billions of dollars. From such types of activities the government is not capable to collect tax liabilities and results budget becomes inept. The business operation by unregistered entities and operators, especially in area of retail services and construction may significantly distort the competition. These types of activities may encourage legal entities to undertake illegal actions to generate revenues aiming to achieve a sustainable position in market. The audit services of certain departments for employment and trade unfortunately are oriented in auditing only entities and operators that are legal and registered whereas as far as illegal activities that take place in theirs eyes it almost doesn’t exist at all. It is a duty of governmental bodies to commit themselves seriously in order to prevent this negative social phenomenon as well as to combat by issuing appropriate legal-economical instruments which primarily would encourage the entities and operators through a micro-credit programs aiming to legalize their economic activities , creation of a guarantee fund by undertaking partially the risk during the first period of business aiming to promote the legalization and to facilitate operating costs within the legal market.
Keywords: informal economy, legal provisions, government, taxes, budget